Clostridioides difficile infection in pediatric inflammatory bowel disease: current understanding and clinical challenges - Rogalidou, Maria (Frontiers in Pediatrics, 2026)
Clostridioides difficile infection (CDI) represents a significant and increasingly recognized complication in children with inflammatory bowel disease (IBD), contributing to prolonged hospitalization and risk of adverse outcomes. Children with IBD are particularly susceptible due to frequent antibiotic exposure, healthcare system contact, immunosuppressive therapy, and underlying gut dysbiosis, all of which promote colonization and toxin-mediated intestinal injury. Distinguishing CDI from an IBD flare is challenging, as gastrointestinal symptoms and systemic inflammation overlap, and asymptomatic toxigenic colonization is common. Management recommendations for pediatric IBD-associated CDI are largely extrapolated from adult studies, with prompt initiation of targeted antibiotics being critical. Immunosuppressive therapy is generally continued, with escalation considered if diarrhea persists despite CDI-directed therapy. Fecal microbiota transplantation (FMT) has emerged as a safe and promising option for recurrent CDI in children with IBD, although careful patient selection, donor choice, and timing remain crucial. Key challenges persist in differentiating true CDI from IBD flares, understanding the clinical impact of asymptomatic colonization, and optimizing microbiome-targeted interventions. Future research should prioritize biomarker-driven diagnosis, individualized therapeutic strategies, and longitudinal evaluation of microbiome-based treatments to improve outcomes in pediatric patients with concurrent CDI and IBD.